Performance Evaluation of Pakistan’s Oil & Gas Regulatory Authority - Zeb, Anwar; Haider, Azad; Hussain, Jawad; Khan, Mudassir Zaman; Shaheen, Farzana; Israr, Muhammad (International Journal of Energy Economics and Policy, 2017)
The purpose of the study was to the evaluate the current performance of Oil & Gas Regulatory Authority (OGRA), which is the regulatory body in mid & downstream of petroleum sector in Pakistan. For attaining the objective of the study, high level petroleum experts were selected through random sampling. Half of the selected experts were from inside OGRA and remaining half from outside the OGRA. The criteria designed by Stern and Holder were used for performance evaluation. The empirical results of the study show that OGRA’s current performance is below the required standards with core issue of less autonomy. It is highly required to have a single autonomious regulatory body for up, mid and downstream of petroelum sector in Pakistan. Keywords: OGRA, Petroleum Sector, Current Performance, Composite Performance Index, Pakistan JEL Classifications: Q4, Q2, Q48